2015
DOI: 10.4103/0975-7406.163567
|View full text |Cite
|
Sign up to set email alerts
|

Lip repositioning surgery for correction of excessive gingival display

Abstract: Esthetic demands have considerably increased over the years in routine clinical practice. A pleasant smile can give supreme confidence to an individuals personality. However, a perfect smile is dictated by a perfect balance of the white (teeth) and pink (gingival) display. This balance can be managed different treatment modalities, which is based on proper diagnosis. This case report demonstrates a successful management of gummy smile with a lip-repositioning procedure in a patient with an incompetent upper li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 6 publications
(5 reference statements)
0
5
0
6
Order By: Relevance
“…However, one comparative study reported better results with a full-thickness approach 51 . Some authors used additional interventions including crown lengthening 47 , 50 - 53 , 57 , 60 and frenectomy 8 , 23 , 33 , 37 , 52 , 54 , 57 to achieve more favorable results with higher stability. Alammar et al 51 mentioned two cases with complete relapse in their conventional surgical group.…”
Section: Resultsmentioning
confidence: 99%
“…However, one comparative study reported better results with a full-thickness approach 51 . Some authors used additional interventions including crown lengthening 47 , 50 - 53 , 57 , 60 and frenectomy 8 , 23 , 33 , 37 , 52 , 54 , 57 to achieve more favorable results with higher stability. Alammar et al 51 mentioned two cases with complete relapse in their conventional surgical group.…”
Section: Resultsmentioning
confidence: 99%
“…Em relação a técnica cirúrgica, são necessários, segundo os artigos analisados, cuidados pré-operatórios como assepsia, analgesia e anestesia local além da antibioticoterapia profilática quando indicada. Depois da cirurgia é imprescindível minimizar a dor, o risco de infecção e inflamação de maneira a tornas o pós operatório confortável (MUTHUKUMAR et al (2015).…”
Section: Discussão Dos Resultadosunclassified
“…Case series and case reports were the most retrieved articles, and there were a limited number of well-designed studies. Some of the case series and most of the case reports reported subjective gingival display reduction without an exact measurement of pre- or postoperative gingival display [ 10 , 30 , 32 , 34 , 36 , 39 , 40 , 42 , 44 , 47 , 49 , 53 , 54 , 58 ]. In the current study, there is lack of sufficient evidence in each modality in order to obtain conclusive results about the gingival display change from baseline to 3, 6, and 12 months after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…However, we did not find any established definition for complete relapse or stability of the results for each patient who undergone LRS. For a number of studies, the stability of the results was not defined by the authors; nevertheless, in the result section, the treatment outcome was reported as stable [ 12 , 36 , 39 , 40 , 42 , 46 , 51 56 , 58 ]. Therefore, stability and complete relapse outcomes in the current study were defined based on the judgment of the experts (NM and SY).…”
Section: Discussionmentioning
confidence: 99%